The Routledge international handbook of economic sociology - Zafirovski, Milan 1958- (Routledge, Taylor & Francis Group, 2023)
This handbook presents a systematic and comprehensive overview of economic sociology, an exemplary interdisciplinary field which draws on theoretical frameworks and empirical findings from both economics and sociology to present a unique lens on the interdependence of the economy and society.
Keywords: Wirtschaftssoziologie; Electronic books; Aufsatzsammlung